Melamine Trisulfonic Acid as a Highly Efficient and Reusable Catalyst for the Synthesis of β-Acetamido Ketones - Abdolkarim Zare (E-Journal of Chemistry)
A highly efficient protocol for the one-pot multi-component condensation of acetophenones with aromatic aldehydes, acetonitrile and acetyl chloride in the presence of melamine trisulfonic acid (MTSA) as a highly efficient and recyclable sulfonic acid-containing catalyst at room temperature is described. In this method, β-acetamido ketone derivatives are obtained in high to excellent yields and in relatively short reaction times.